Autapomorphies in the generic classification of Plectrothripini (Thysanoptera, Phlaeothripinae), with a new genus and a new record from Malaysia - Mound, L.a.; Ng, Y. F. (Zootaxa, 2018)
Bangithrips mei gen. et sp. n. is described from Peninsular Malaysia. The significance is discussed of outstanding structural autapomorphies that are commonly used in classifications of Thysanoptera. Argyrothrips ommatos described recently from northern Australia is recorded from Malaysia.